Lipolymphedema Associated with Idiopathic Cyclic Edema: A Therapeutic Approach - Jose Maria Pereira de Godoy; Henrique Jose Pereira de Godoy; Aline Aparecida de Sene Souza; Ricardo Budtinger Filho; Maria de Fatima Guerreiro Godoy (Case Reports in Vascular Medicine)
Idiopathic cyclic edema is a type of generalized edema that mainly affects women. Diagnosis is made by the patient’s clinical history and an evaluation of the accumulation of weight during the day. The objective of this study is to report the clinical control of lymphedema associated with idiopathic cyclic edema using calcium dobesilate. A 55-year-old female patient reported generalized edema for years in that she woke up in the morning with her legs swollen and the edema worsened during the day. The physical examination revealed generalized edema. After four days of treatment with calcium dobesilate, the patient returned to the Clínica Godoy, Brazil, with less edema and reductions in body weight and the amount of extracellular and intracellular fluid. With further treatment, there was a total reduction of the edema. It is concluded that calcium dobesilate helps to control lymphedema secondary to idiopathic cyclic edema.